Preventive behavior of sexually transmitted diseases among high school students in Vientiane, Lao P.D.R - Khitthiphong, Viengsavanh; Hongkailert, Nate; Sillabutra, Jutatip Sillabutra (Journal of Public Health and Development, 2014)
This study was conducted in Vientiane Capital City, Lao P.D.R. The study aimed to identify preven- tive behavior regarding sexually transmitted diseases (STDs). The study sample was 275 high school students of grades 5-7 by using simple random sampling.The data were collected by using a self-administered questionnaire and analyzed by using descriptive statistics and multiple logistic regressions. A questionnaire consisted of 5 parts:- Socio-demographic, communication towards STDs, perception of STDs preventive, knowledge of STDs and behavior, and STDs preventive, The study revealed that the average age of the respondents was 17.23 years old (SD = 0.99), and the range of age was 15-19 years old. About 51% were male. The majority of them (81.1%) stayed with their parents. Most of them (60.7%) practiced good STDs preventive behavior. Communication towards STDs preventive was significantly associated with STDs preventive behavior (OR = 2.37, 95% CI = 1.30-3.71) when adjusting for other factors in the model. Regarding the findings, it is necessary to provide appropriate STDs and safe sex education among high school students and arrange a proper environment in which students are able to discuss sexual and related problems with their teachers. It is also important to encourage them to continuously practise safe sex for STDs preventive since they had good STDs preventive behavior.